Pengaruh Pendapatan Asli Daerah dan Dana Tranfer ke Daerah Terhadap Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia di Wilayah Sulampua - Muammil Sun’an; Aziz Hasyim; Yetty Yetty (Lembaga Teewan Journal Solutions, 2026)
This study contributes to the empirical literature on fiscal decentralization by examining the role of regional fiscal capacity and intergovernmental transfers in driving economic growth and human development in eastern Indonesia, particularly Sulawesi. This study aims to analyze the influence of Original Regional Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on economic growth and the Human Development Index (PJK). This study uses a quantitative approach using panel data from 10 provinces in Sulawesi during 2017–2024. The analysis uses Fixed Effects Model (FEM) estimation with model selection tests, including the Chow, Hausman, and Lagrange Multiplier tests. The results show that PAD and DAK have a positive and significant effect on economic growth and PJK. DBH has a positive effect on economic growth but does not significantly affect PJK, while DAU does not show a significant impact on either indicator. Strengthening regional fiscal capacity and increasing the effectiveness of transfer fund allocation are important strategies to accelerate sustainable development in eastern Indonesia